2014
DOI: 10.3389/fpls.2014.00451
|View full text |Cite
|
Sign up to set email alerts
|

Injury and immune response: applying the danger theory to mosquitoes

Abstract: The insect immune response can be activated by the recognition of both non-self and molecular by-products of tissue damage. Since pathogens and tissue damage usually arise at the same time during infection, the specific mechanisms of the immune response to microorganisms, and to tissue damage have not been unraveled. Consequently, some aspects of damage caused by microorganisms in vector-borne arthropods have been neglected. We herein reassess the Anopheles–Plasmodium interaction, incorporating Matzinger’s dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 145 publications
1
13
0
1
Order By: Relevance
“…Interestingly, our data show that eATP induces conidiation in response to injury and suggest that eATP is an important signal molecule that is released from damaged hyphae. Thus, eATP can also be considered a damage signaling molecule in fungi, which plays a similar role in wound signaling to that reported in triggering immune responses in mammals ( Chen and Nuñez, 2010 ; Zeiser et al, 2011 ; Cordeiro and Jacinto, 2013 ), fish ( Kawate et al, 2009 ), insects ( Moreno-García et al, 2014 ), algae ( Torres et al, 2008 ), and plants ( Chivasa et al, 2009 ). Elevations in the concentration of intracellular calcium have also been observed in Arabidopsis upon application of eATP ( Tanaka et al, 2010 ).…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, our data show that eATP induces conidiation in response to injury and suggest that eATP is an important signal molecule that is released from damaged hyphae. Thus, eATP can also be considered a damage signaling molecule in fungi, which plays a similar role in wound signaling to that reported in triggering immune responses in mammals ( Chen and Nuñez, 2010 ; Zeiser et al, 2011 ; Cordeiro and Jacinto, 2013 ), fish ( Kawate et al, 2009 ), insects ( Moreno-García et al, 2014 ), algae ( Torres et al, 2008 ), and plants ( Chivasa et al, 2009 ). Elevations in the concentration of intracellular calcium have also been observed in Arabidopsis upon application of eATP ( Tanaka et al, 2010 ).…”
Section: Discussionmentioning
confidence: 77%
“…However, it seems that in A. aegypti the concurrence of damage and the pathogen leaded to an optimal immune response. Several DAMPs have been found in insects ( Moreno-García et al, 2014b ). It will be very interesting to determine the DAMPs particularly involved in the A. aegypti ’s priming against bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that wild type or laboratory-reared mosquito midgut is housed by a variety of bacteria (Minard et al, 2013; Kajla et al, 2015a) and their interaction with different development stages of Plasmodium also determines the mosquito cycle of the parasite (Touré et al, 2000; Dong et al, 2009; Cirimotich et al, 2011b; Wang et al, 2011; Boissière et al, 2012; Moreno-García et al, 2014). In addition, the type and number of bacteria also vary during different development stages and habitat of the mosquito (Wang et al, 2011; Minard et al, 2013; Kajla et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%